Online Brand Attachment, Experience, and Sales Promotion Leads to Purchase Intention: Moderating Role of Online Brand Trust - Saqib Mehmood; Madiha Hamid (Journal of Management Practices, Humanities and Social Sciences, 2024)
This research examines the impact of online brand experience on online brand trust and online repurchase intention. Additionally, the study tests whether online brand attachment moderates these influences. The study provides insights for online retail store managers to focus on improving the online experience for their customers to promote online brand trust and online repurchase intentions. This quantitative research, conducted as a cross-sectional study, investigates the dynamics of online consumer behaviour within the context of the Daraz online website in Pakistan. The study encompasses 530 participants who actively engage as shoppers on the platform. Utilizing a survey-based approach, the research explores the interplay between online brand attachment, online brand experience, purchase intention, the moderating role of online brand trust, and the mediating role of sale promotion. Employing the Smart PLS method for data analysis, the study contributes to the evolution of attachment theory within the digital marketing landscape. The background of the research centres on the unique online shopping environment provided by Daraz, a prominent online marketplace in Pakistan. The findings offer valuable insights for marketers seeking to enhance brand management strategies and optimize the online shopping experience to drive consumer attachment and purchase intentions in the competitive E-commerce landscape.